A Comparative Study of the Duty of Loyalty of Company Directors and Its Impact on Conflict of Interest Management and Data Retention in Iranian and English Law - mohammadreza Pasban; salah mahmoodi (پژوهشهای حقوقی)
Today, in the common law system, in order to secure the interests of the shareholders and preserve the company's information, compliance with the "duty of loyalty" is considered the most important regulation for managers. This regulation plays an essential role in the compliance and compatibility of managers' obligations with other legal systems. Based on this, considering the foundation of this concept based on the fiduciary principles in the common law system, it can be used as a fundamental concept in the corporate law of Iran and other countries. In addition to the fact that the rules of corporate governance and the theory of the independence of managers are the result of the development and impact of the Common Law system in the matter of fulfilling the duty of loyalty and dealing with conflict of interests, the penetration of these rules into Iranian law in the laws of commerce (1311 and 1347) and the securities market (1384) ), in addition to checking and legal review, it sometimes requires revision and modification of the texts of these laws. In this research, for the first time, relying on the analytical-comparative method and after stating some key issues, it is attempted to investigate and analyze the way to ensure the duty of loyalty and at the same time the examples of its violation, in the issue of conflict of interest management and information preservation. Legal solutions companies should be inferred.